(untitled) (Universal International Scientific Journal, 2026)
This article reveals the theoretical foundations and modern trends in the use of scientific and analytical research in the process of legal policy formation and the importance of using an evidence-based approach, numerical analysis tools, comparative legal methods, forecasting technologies, and social research results in the development of legal policy.